Interferensi Fonologis Bahasa Indonesia terhadap Bahasa Arab pada Pembacaan Surah al-Fātiḥah - Karimah, Inayatul; Letmiros, Letmiros; Hajidah, Gina Najjah (Kalimatuna: Journal of Arabic Research, 2022)
This study aims to reveal the form of phonological interference of Indonesian to Arabic and the magnitude of frequency of phonemes that experience said phonological interference in the reading of Surah al-Fātiḥah by non-Islamic boarding school students (Pesantren) of the Arabic Studies Program at the University of Indonesia. The research methodology that was used is a qualitative research method with a descriptive approach. The primary data of this study came from questionnaires and respondent interviews while the secondary data came from library research such as books and literature that is related to the topics in question.  The results of this study indicate that there are several sound deviations made by the respondents; there is one vocalist interference in the vowel, and there are 12 phonological interferences in consonants. The highest frequency of consonant interference is in consonant ح/ħ/ by 11.60%, and the lowest at consonant ء/?/ by 0.44%.